086 A UK multicentre audit on the use of MRI in multiple sclerosis. Issue 6 (27th May 2022) - Allen, Christopher; Fernandes, Linford; Williams, Thomas; Chataway, Jeremy; Evangelou, Nikos; Tallantyre, Emma; Ford, Helen; ,; ,
Abstract : The contemporary use of MRI in the care of 2567 persons with multiple sclerosis (MS) was audited in 25 MS centres, from all four UK nations. Variation in practice has an impact on patient care and implica- tions for service design. Routine monitoring of all MS patients accounted for 45% of MRI scans, and the mean inter-scan interval varied by centre from 12 to 32 months, a wide variation in practice. For routine monitoring scans, the detection of one new MS lesion was associated with 30% of patients subsequently changing disease- modifying treatment (DMT); this increased to 52% when ≥2 new lesions were reported. Unfortunately, only half of patients requiring progressive multifocal leukoencephalopathy surveillance were scanned at the recommended frequency. Most MRI scans are performed within ten years of diagnosis. With DMT now available for all stages of MS, this will lead to significant additional MRI utilisation. Spinal imaging was included in half of routine moni- toring scans; this had no measureable impact on DMT decision-making. Neither did it have any impact on detection of radiological dissemination in time for diagnostic scans. This suggests that its use could be safely restricted to help meet the additional capacity required. christopher: allen@nottingham.ac.uk|ABN Bursary 68